2006
DOI: 10.1089/thy.2006.16.1303
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation in the Thyrotropin (Thyroid-Stimulating Hormone) Receptor Gene in a Case of Congenital Hypothyroidism

Abstract: Congenital hypothyroidism (CH) occurs approximately with a frequency of 1 in 3000-4000 births, being a disease caused by defects in thyroid hormone synthesis associated either with goiter presence or with agenesis or ectopy of the thyroid gland. A study of some familial cases has allowed identification of mutations in several known genes, including that encode the thyroid-stimulating hormone receptor (TSHR). We report a familial case of CH that transmitted as a recessive trait and caused by a novel homozygous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Resistance to TSH may be caused by various molecular mechanisms. Homozygous or compound heterozygous inactivating mutation in TSHR have been found in several patients with overt hypothyroidism and thyroid hypoplasia [11][12][13][14] . We hypothesize that individuals in whom one of the TSHR alleles has compromised function may be predisposed to subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to TSH may be caused by various molecular mechanisms. Homozygous or compound heterozygous inactivating mutation in TSHR have been found in several patients with overt hypothyroidism and thyroid hypoplasia [11][12][13][14] . We hypothesize that individuals in whom one of the TSHR alleles has compromised function may be predisposed to subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…The first mutation in the human TSHR gene in patients with CH was described by Sunthornthepvarakul [3]. After this report,many other mutations were discovered in patients with variable TSH unresponsiveness and different thyroid developmental status [2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In some of these patients [3][4][5][6][7][8][9], TSH resistance was exemplified by normal free thyroid hormones with elevated TSH levels (defined as compensated hypothyroidism or subclinical hypothyroidism) and a normal or hypoplastic thyroid gland.…”
mentioning
confidence: 99%
“…At the other end of the spectrum, severe biochemical hypothyroidism associated with a hypoplastic thyroid gland or even apparent athyreosis has been reported [2,[13][14][15][16][17][18][19][20]. Inactivating mutations in the human TSHR gene are therefore associated with three phenotypes [2]: (i) fully compensated TSH resistance (subclinical hypothyroidism) (ii) partially compensated TSH resistance (mild hypothyroidism) (iii) severe uncompensated resistance to TSH (severe hypothyroidism).…”
mentioning
confidence: 99%
“…The degree of CH is variable and depends on the genotype. Severe forms manifest as overt CH (Bretones et al, 2001;Gagne et al, 1998;Jeziorowska et al, 2006;Park et al, 2004;Tonacchera et al, 2000), moderate forms as hypothyroidism identified by neonatal screening without clinical symptoms of hypothyroidism (Abramowicz et al, 1997;Jordan et al, 2003), and mild forms present with hyperthyrotropinemia and normal thyroid hormones (de Roux et al, 1996;Nagashima et al, 2001;Narumi et al, 2009;Tenenbaum-Rakover et al, 2009). Gagne et al (1998) described a case of CH with persistent neonatal jaundice, myxedematous facies, large fontanelle and absence of ossification centers of the knee on x-rays, indicating severe prenatal deficiency of thyroid hormone.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…It was only in 1995 that the cause for RTSH syndrome in that case was shown to be a mutation in TSHR (Sunthornthepvarakul et al, 1995). Since the first report of CH caused by a TSHR mutation, several cases of loss-offunction mutations of TSHR have been reported: most are missense mutations, but deletions and insertions have been identified as well (see http: www.hgmd.cf.ac.uk/ac/ gene.php?gene=TSHR and OMIM#275200) (Abramowicz et al, 1997;Alberti et al, 2002;Biebermann et al, 1997Biebermann et al, , 2010Bretones et al, 2001;Camilot et al, 2005;Cangul et al, 2010;Clifton-Bligh et al, 1997;De Marco et al, 2009;de Roux et al, 1996;Fricke-Otto et al, 2005;Gagne et al, 1998;Grasberger et al, 2007;Jeziorowska et al, 2006;Jordan et al, 2003;Kanda et al, 2006;Nagashima et al, 2001;Narumi et al, 2009;Narumi et al, 2011;Park et al, 2004; …”
Section: Introductionmentioning
confidence: 99%